Promising Physical, Physicochemical, and Biochemical Background Contained in Peels of Prickly Pear Fruit Growing under Hard Ecological Conditions in the Mediterranean Countries. (27th December 2019) - Bourhia, Mohammed; Elmahdaoui, Hamza; Ullah, Riaz; Bari, Ahmed; Benbacer, Laila
Abstract : Background . Prickly pear ( Opuntia spp.), called Barbary fig, is a cultivated species springing from family Cactaceae . It is native to Mexico and has been naturalized in other continents, especially the Mediterranean countries (North Africa). The aim of the study was to investigate the physical, physicochemical, and biochemical criteria of peels of three Moroccan prickly pear varieties (Aakria, Derbana, and Mles) growing in the Rhamna regions (dry area). Material and Methods . Both physicochemical characteristics (humidity, water activity, Brix, ash content, pH, and total titratable acidity) and biochemical characteristics (total carotenoid content, betalain content, total polyphenolic content, and ascorbic acid content) were were studied according to previously reported methods. Results . Regarding the physiochemical criteria, the moisture of the fresh peels of studied varieties ranged from 81.59 ± 0.02 to 83.47 ± 0.02%. The water activity (aw) ranged from 0.862 ± 0.001 to 0.872 ± 0.001. The values of Brix varied from 14.69 ± 0.05° Bx to 15.80 ± 0.03° Bx. pH values varied from 5.13 ± 0.01 to 5.32. The total titratable acidity values ranged from 0.130 ± 0.008 to 0.196 ± 0.014 g of citric acid/100 g of FM (fresh matter). The ash content values ranged from 8.92 ± 0.10 to 11.04 ± 0.06 g/100 g of FM. Regarding the biochemical criteria, the total carotenoid content ranged from 2.29 ± 0.01 to 2.87 ± 0.01 μ g/g of FM. The total betalain content ranged from 6213.46 ± 58.86 to 8487.19 ± 51.71 μ g/100 g of FM. The total polyphenolic content varied from 160 ± 3.55 to 243.79 ± 5.55 mg GA E/100 g of FM. The ascorbic content ranged from 58.21 ± 0.24 to 74.72 ± 0.17 mg/100 g of FM. Conclusion . The findings of physicochemical and biochemical criteria of the investigated varieties growing in Moroccan drylands showed promising results in terms of studied parameters.